Theoretical Problems of Periodization of Literature - Aleksić, Slađana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
An overview of epochs and directions is not the history of literature, because history cannot be reduced to summary representations of periods and directions. The greatest writers, the creators of history, are above and beyond the directions and schools. Directions and schools appear and disappear legally, so they are imposed as a subject of literary-historical and theoretical study. The periodization system establishes a certain scientific orientation in a multitude of literary facts, past and present. The paper highlights the theoretical problem of periodization of literature, as a central problem of theoretical examinations of literary phenomena.
Keywords: literary historiography; historicism; epoch; direction; time; space